P515 Manipulating the microbiome in paediatric acute severe colitis with a cocktail of antibiotics: A pilot randomised controlled trial. (16th January 2018) - Turner, D; Vlamakis, H; Marcus, D; Yassour, M; Bishai, J; Yerushalmi, B; Griffiths, A; Aloi, M; Albenberg, L; Kolho, K -L; Abutbul, G; Assa, A; et al.
Abstract: Background: A previous case series suggested a benefit of antibiotic-cocktail in steroid-refractory paediatric UC. In this pilot randomised investigator-blinded controlled trial we aimed to evaluate the effectiveness of wide-spectrum antibiotic regimens in acute severe colitis (ASC) in addition to standard intravenous corticosteroid (IVCS) therapy. Methods: Children 2–18 years with ASC (i.e. PUCAI ≥ 65) refractory to oral steroids were randomised into two arms: the first received antibiotics in addition to IVCS (amoxicillin, vancomycin, metronidazole, doxycyclin (or ciprofloxacin in those younger than 8 years of age)-AB+IVCS), while the other received only IVCS. Children with proctitis, infections, and those treated with antibiotics in the preceding 2 weeks were excluded. The primary outcome was total PUCAI score at Day 5 of treatment. Missing data for ITT analysis were imputed using the NRI method for categorical variables and LOCF for continuous variables. Results: Thirty children were randomised and two were excluded (one positive for CMV and one salmonella): 16 in the AB+IVCS and 12 in the IVCS arms (mean age 14 ± 2.7 years, range 7–18, 15 (54%) males, 23 (82%) extensive colitis). Baseline variables were similar between groups (PUCAI 73.1 ± 6.6 vs. 75 ± 7.1, respectively). The mean Day 5 PUCAI was 25 ± 16.7 vs. 40.4 ± 20.4, respectively ( p = 0.037). Bearing in mind that the trial was not powered for this, there were no differences in the need for second-line therapy during the admission nor in the colectomy rate 1 year following admission (19% vs. 17%; p = 0.89). Median admission days (IQR) was statistically similar (7.5 (5–10) vs. 9 (5.5–13); p = 0.35). Microbiome analysis upon admission was available for 22 children of whom 8 (36%) had a predominant bacterium (>33% abundance). Conclusions: In this RCT, the first ever performed in children with ASC, antibiotic cocktail in addition to IVCS improved disease activity on Day 5. Further studies are needed to determine whether this is associated with improved long-term hard outcomes.